2013
DOI: 10.1097/ede.0b013e3182a6d9aa
|View full text |Cite|
|
Sign up to set email alerts
|

Immortal Time Bias in the Study of Stillbirth Risk Factors

Abstract: Immortal time before diagnosis of gestational diabetes may bias our understanding of the stillbirth risk associated with this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 17 publications
4
22
0
Order By: Relevance
“…Most recent studies have indicated the absence of increased risk [5,8], but these studies did not take immortality bias into account. In the study by Hutcheon et al [14], the RR for stillbirth among women with GDM was 1.25 in analyses limited to births after 28 weeks. In our study, the risk of perinatal mortality was not increased among deliveries after 28 weeks: surprisingly, it was increased only among deliveries after 37 weeks, whether or not women were insulin-treated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recent studies have indicated the absence of increased risk [5,8], but these studies did not take immortality bias into account. In the study by Hutcheon et al [14], the RR for stillbirth among women with GDM was 1.25 in analyses limited to births after 28 weeks. In our study, the risk of perinatal mortality was not increased among deliveries after 28 weeks: surprisingly, it was increased only among deliveries after 37 weeks, whether or not women were insulin-treated.…”
Section: Discussionmentioning
confidence: 99%
“…Immortal time refers to the follow-up time during which, because of the exposure definition, the outcome under study could not occur, corresponding to the time prior to the diagnosis of GDM [13]. As highlighted by Hutcheon et al, differences at the start of follow-up between women with and without GDM can lead to overestimation of the perinatal mortality rate in the population without diabetes [14]. This bias can also affect risk estimation for other outcomes that may occur before the start of the GDM screening period.…”
Section: Outcomes For Neonatesmentioning
confidence: 99%
“…Similarly, this study found increased risk of stillbirth due to gestational diabetes from 28 weeks onwards, in concordance with Hutcheon and colleagues [233]. It has been argued that the 'protective' effect observed in relation to gestational diabetes at earlier gestational ages may be due to routine screening for GDM around 24-28 weeks [233]. There is evidence of higher rates of increase in gestational diabetes among non-Indigenous women, despite currently lower absolute rates of GDM compared with Indigenous women [87].…”
Section: Interpretation Of Findings Diabetessupporting
confidence: 80%
“…Furthermore, there was disparity in the population attributable fractions associated with pre-existing diabetes among Indigenous and non-Indigenous women (7.4% vs 1.6%); however, these were similar to those reported for other high income countries (3-5%) [32]. Similarly, this study found increased risk of stillbirth due to gestational diabetes from 28 weeks onwards, in concordance with Hutcheon and colleagues [233]. It has been argued that the 'protective' effect observed in relation to gestational diabetes at earlier gestational ages may be due to routine screening for GDM around 24-28 weeks [233].…”
Section: Interpretation Of Findings Diabetessupporting
confidence: 80%
“…One problem with the example (acknowledged by the authors as a limitation) relates to a temporal issue involving the determinant and the outcome. Most women who develop preeclampsia do so after 37 weeks' gestation and therefore an immortal time bias plagues the preeclampsia‐preterm birth association . Unfortunately, as Bandoli et al mention, absence of information on gestational age at which the diagnosis of preeclampsia occurred precluded restriction of preeclampsia cases to those with a diagnosis prior to 37 weeks.…”
Section: Critique Of the Preeclampsia‐preterm Birth Examplementioning
confidence: 99%